2020
DOI: 10.3390/jfb11030065
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatibility of α-Al2O3 Ceramic Substrates with Human Neural Precursor Cells

Abstract: Background: Biocompatible materials-topography could be used for the construction of scaffolds allowing the three-dimensional (3D) organization of human stem cells into functional tissue-like structures with a defined architecture. Methods: Structural characterization of an alumina-based substrate was performed through XRD, Brunauer–Emmett–Teller (BET) analysis, scanning electron microscopy (SEM), and wettability measurements. Biocompatibility of the substrate was assessed by measuring the proliferation and di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…Selecting Al 2 O 3 as model material was reasoned by being produced in the largest quantity among advanced ceramics. Moreover, its application field can be greatly broadened as functionally graded material especially in medicine [20][21][22][23]. The good mechanical properties combined with bioinertness make alumina an appealing material of choice for several medical applications such as bearings in hip replacement [24] or dental implants [25], but a graded microstructure would be an additional advantage.…”
Section: Introductionmentioning
confidence: 99%
“…Selecting Al 2 O 3 as model material was reasoned by being produced in the largest quantity among advanced ceramics. Moreover, its application field can be greatly broadened as functionally graded material especially in medicine [20][21][22][23]. The good mechanical properties combined with bioinertness make alumina an appealing material of choice for several medical applications such as bearings in hip replacement [24] or dental implants [25], but a graded microstructure would be an additional advantage.…”
Section: Introductionmentioning
confidence: 99%
“…The cells almost doubled in number within 13 days of culture ( Figure 10 b). We have previously shown that human NPCs cultured on 2D alumina substrates efficiently differentiate into neuronal populations and form a functional neuronal network [ 32 ]. Therefore, NPCs grown on 3D-printed ceramic scaffolds were spontaneously differentiated for 21 days (day 34 post-seeding) as well.…”
Section: Resultsmentioning
confidence: 99%
“…The in situ XRD was a D8 Advance from Bruker equipped with Cu Ka radiation source from 5–80 2θ angle with 0.04 step and the high temperature oven was a HTK 1200N from Anton Paar. The wetting ability of the ceramic material was measured by the water contact angle method in an in-house contact angle measurement instrument based on a high-resolution sensor camera (Nikon D5600, Tokyo, Japan, AF-P NIKKOR 18–55 mm 1:3.5–5.6 G) according to the arrangement proposed in [ 32 ]. Micro-droplets (2.5 μL) of a double distilled water drop were added manually via a variable volume 0–20 µL Eppendorf Research micropipette.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations